The Effect Of Sustainability Reporting, Environmental Performance And Media Exposure On Reputation Of Food And Beverage Sector Companies Listed The Indonesia Stock Exchange - Indriyanti, Vivin Lauren; Dura, Justita (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study examines the influence of sustainability reporting, environmental performance, and media exposure on corporate reputation in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The topic is relevant due to the growing emphasis on sustainable business practices and the increasing demand from investors for non-financial information reflecting corporate social and environmental responsibility. Background Problems: The research addresses the question of whether sustainability reporting, environmental performance, and media exposure significantly affect corporate reputation within the food and beverage industry. Research Methods: A quantitative approach with an explanatory research design was employed. The sample consists of 81 companies selected through purposive sampling for the 2022–2024 period. Data analysis was conducted using classical assumption tests and multiple linear regression with SPSS version 25. Finding/Results: The findings indicate that sustainability reporting has a positive and statistically significant effect on corporate reputation. In contrast, environmental performance and media exposure do not show a significant influence on corporate reputation. Conclusion: The study concludes that sustainability reporting plays a crucial role in enhancing corporate reputation, while environmental performance and media exposure are less impactful. These results imply that companies should prioritize transparent sustainability reporting to strengthen their reputation among stakeholders.